2015
DOI: 10.1186/s40478-015-0243-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of robust satellite cell activation and muscle regeneration during the progression of Pompe disease

Abstract: IntroductionMuscle stem cells termed satellite cells are essential for muscle regeneration. A central question in many neuromuscular disorders is why satellite cells are unable to prevent progressive muscle wasting. We have analyzed muscle fiber pathology and the satellite cell response in Pompe disease, a metabolic myopathy caused by acid alpha-glucosidase deficiency and lysosomal glycogen accumulation. Pathology included muscle fiber vacuolization, loss of cross striation, and immune cell infiltration.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…In addition, periodic acid-Schiff (PAS) staining showed minor glycogen accumulation ( Figure S3). These findings suggested that the patient might have late-onset Pompe disease, 24 but there were two inconsistencies: the lack of GAA deficiency in lymphocytes and the LVH, a characteristic of the classic infantile phenotype but not late-onset Pompe disease.…”
Section: Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, periodic acid-Schiff (PAS) staining showed minor glycogen accumulation ( Figure S3). These findings suggested that the patient might have late-onset Pompe disease, 24 but there were two inconsistencies: the lack of GAA deficiency in lymphocytes and the LVH, a characteristic of the classic infantile phenotype but not late-onset Pompe disease.…”
Section: Patientmentioning
confidence: 99%
“…39 PAS staining was performed on sections of glycolmethacrylate (GMA)-processed tissue. 24 Hematoxylin and eosin (H&E) stainings were performed on both GMA fixated and cryosections. A Hamamatsu NanoZoomer 2.0 (Hamamatsu Photonics) was used for imaging, and images were analyzed with NDP.view software.…”
Section: Histology and Imagingmentioning
confidence: 99%
“…In this model, overexpression and knockdown of HOXA9 were mediated through plasmids and detected 36h after transfected, showing a satisfactory overexpression average 4.16-fold at protein levels and 2750.83-fold at mRNA levels, and knockdown to 42.69% at protein levels and 48.75% at mRNA levels ( figure 3.B-E). [19,20], showed inhibited averagely to 38.29% (Myod) and 79.97% (Myogenin) by pIRES2-DsRed2-HOXA9 plasmids, while pPLK/GFP-Puro-HOXA9 shRNA plasmids could rescue them to 116.10% (Myod) and 137.24% (Myogenin) ( figure 4. A-C).…”
Section: In Vitro Analysis Of Hoxa9 Effects On Satellite Cellsmentioning
confidence: 99%
“…All data were obtained and analyzed with Image Pro Plus 6.0 software. For immunostaining, the para n sections of muscle tissue were dewaxed as previously described [34], placed in a solution of sodium citrate at 100 °C for 10 minutes and then soaked in hydrogen peroxide. Cross-section samples were immunostained with mouse monoclonal anti-SaCas9 primary antibody (1:200, Epigentek, catalogue number: A-9001) and goat anti-mouse IgG-FITC (1:500, Abcam, catalogue number: ab6785) secondary antibody, and DAPI for nuclei.…”
Section: Protein Analysismentioning
confidence: 99%